PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) MENGGUNAKAN MEDIA CARD THINK DALAM PEMBELAJARAN MATEMATIKA TERHADAP PEMAHAMAN NUMERASI SISWA DI KELAS III SD - Pakar, Deavani Farida; Nurasiah, Iis; Maulana, Lutfi Hamdani (STKIP Persada Khatulistiwa Sintang, 2024)
The research aims to determine the effect of the contextual teaching and learning model with the help of card think media on students' understanding of numeracy in class III in learning mathematics at SD Negeri Dewi Sartika CBM Sukabumi City. The method used is an experiment, namely a quasi-experimental design with a pretest posttest nonequivalent control group. The research population was class III students at Dewi Sartika CBM Public Elementary School, Sukabumi City, divided into research samples, namely class 3A as the experimental class and class 3B as the control class with the number of each class being 21 students. The data collection technique is in the form of a test, for the data analysis technique used is a two-sample independent T-test. The results obtained for the average posttest score from using the CTL model using card think media was 68.10 and for those who did not use card think media it was 59.90. So the results of hypothesis testing obtained are (0.034<0.05) with a significance level of 0.05 so that H0 is rejected and Ha is accepted. Thus, it can be concluded that the contextual teaching and learning model assisted by card think media has an influence on students' understanding of numeracy in class III mathematics learning in elementary schools.